ELECTORAL ENGINEERING, ETHNICITY AND PRESIDENTIAL ELECTIONS IN NIGERIA, 1979-2007 (2014)
Electoral engineering, the purposeful manipulation of electoral rules, relating to party organisation and electoral formula, has been established in comparative political studies as a tool for managing ethnicity in order to stabilise politics in divided societies. In Nigeria, ethnicity has been a major obstacle to democratic stability. Most studies on policy measures to address ethnicity in Nigeria have focused on federalism, federal character and political restructuring, with little attention paid to the electoral system. This study, therefore, examined the use of electoral engineering tools and their consequences in managing ethnicity in Nigerian politics. A longitudinal case study was employed and this was guided by rational choice institutional theory, with a focus on the structure of electoral incentives. Nigerian presidential elections from 1979 to 2007 were purposively selected. Key Informant Interviews (KII) were conducted, with 12 leaders of six frontline political parties including: National Party of Nigeria (NPN); Unity Party of Nigeria (UPN); National Republican Convention (NRC); Social Democratic Party (SDP); All Peoples Party (APP); and Peoples Democratic Party (PDP) and six experts in electoral system design on the effects of electoral rules on ethnicity and party organisation across the geo-political zones in Nigeria. Secondary data on electoral rules and disaggregated results of presidential elections were collected from archival documents. Data were subjected to content analysis. Innovative changes in the electoral rules since 1979 included: requirements that membership in each party be open to every Nigerian irrespective of ethnic origin; power sharing through rotation of key political offices across zones and the use of two party system; five percent vote pooling electoral requirement for party registration; presidential electoral formula of plurality and 25% geographic distribution of votes in two-third states of the federation. Electoral rules on party formation promoted the development of inter-ethnic bargaining and compromises within the party system. Membership in each of the parties increasingly spread across various ethnic groups. There was a change in the voting behaviour of the electorates. Voting patterns in the presidential elections reflected a progressive decline in the influence of the ethnic factor in Nigeria’s body polity. In 1979, the NPN won the mandatory 25% of votes in 12 of 19 states; in 1983 16 of 19;in 1993 SDP in 28 of 30 states; and NRC 23 of 30; in 1999 PDP 32 of 36; and APP 24 of 36; in 2003 PDP 32 of 36. The KIIs showed that since 1979, the Presidential electoral formulae aided the emergence of national rather than parochial parties as candidates were compelled to campaign acrossethnic platforms. The incentives in the electoral system were perceived to have engendered balance in the distribution of key government and party offices among the six geo-political zones (North-West, North-East, North-Central, South-West, South-East and South-South) and aided inter-ethnic cooperation and inter-group equilibrium. Electoral engineering tools moved Nigerian politics from ethnic parochialism to inclusion and accommodation. These innovative electoral rules should be strengthened in order to enhance democratic stability.